E-Learning (IntechOpen, 2021)
In this book, we can read about new technologies that enhance training and performance; discover new, exciting ways to design and deliver content; and have access to proven strategies, practices and solutions shared by experts. The authors of this book come from all over the world; their ideas, studies, findings and experiences are beneficial contributions to enhance our knowledge in the field of e-learning. The book is divided into three sections, and their respective chapters refer to three macro areas. The first section of the book covers Instructional Design of E-learning, considering methodology and tools for designing e-learning environments and courseware. Also, there are examples of effective ways of gaming and educating. The second section is about Organizational Strategy and Management. The last section deals with the new Developments in E-learning Technology, emphasizing subjects like knowledge building by mobile e-learning systems, cloud computing and new proposals for virtual learning environments/platforms.